2010
DOI: 10.1111/j.1439-0507.2009.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dermatophytes and other related fungi in Jaipur city, with particular reference to soil pH

Abstract: Screening of 217 soil samples of different habitats, such as PG study centre, garden, farmhouse, nursery, roadside, hostel, animal habitat, bird habitat, marriage garden, temple, vegetable market and house dust, was carried out for the presence of dermatophytes and related fungi in relation to soil pH. A total of 461 isolates belonging to 26 genera and 34 species were recorded. Soil pH values vary from 3 to 10.5. Trichophyton verrucosum, Microsporum audouinii and M. canis were isolated for the first time in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Some have a wide range of tolerance for acidic to alkaline soils 2 7 14 16 . However, studies of soil pH in relation to occurrence of dermatophytes are uncommon in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Some have a wide range of tolerance for acidic to alkaline soils 2 7 14 16 . However, studies of soil pH in relation to occurrence of dermatophytes are uncommon in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…This dermatophyte is predominant in very wet soils, a condition which is not present in the soils of Djerba [1,5]. T. terrestre, which was frequent in some studies [4,8,9,16,23], was not isolated in ours and also absent in others [9,16,20,22]. This difference in keratinophilic fungi distribution may be due to the distinct climatic conditions prevalent in these areas [9,10].…”
Section: Discussionmentioning
confidence: 71%
“…It is recognized that their distribution and their dominant species vary according to the soil of different locations [6,8,12,14,16,23]. Only 20.6% of Djerba soils yielded keratinophilic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…No keratinophilic fungi growth was reported below in soil with pH 5.0 and above 8.0. According to a research conducted by Jain and Sharma, most of the keratinophilic fungi were isolated from pH 6.5 to 8.5 (25). Meinhof et al (26) and Kaben et al (27) suggested that highly acidic soils were mostly a poor source of keratinophilic fungi.…”
Section: Discussionmentioning
confidence: 99%